Extender Supplementation with Glutathione (GSH) and Taurine Improves In Vitro Sperm Quality and Antioxidant Status of New Zealand Rabbits during Chilled Storage for up to 72 hours - Mohamed F. F. Bayomy; Sobhy E. Hassab El-Nabi; Tahany A. El Kassas; Zeinab I. Attia; Ayman M. Saeed; Heba S. A. Taha; Mahmoud Alagawany; Livio Galosi; Lucia Biagini; Seham El-Kassas (Veterinary Medicine International)
This study assessed the influence of supplementing the rabbit semen extender with various concentrations of glutathione (GSH) and taurine at 24, 48, and 72 h postchilling at 5°C. Semen samples were collected from 20 New Zealand bucks, and ejaculates with standard color, motility (>85%), about 0.5 mL volume, and ∼400 × 106/mL concentration were used and diluted with extenders supplemented with 0.5, 1, and 2 mM of GSH and 1, 5, and 10 mM of taurine and chilled at 5°C. Nonsupplemented samples were used as a control. Sperm’s progressive motility, acrosome reaction, and extracellular oxidative stress biomarkers such as MDA contents and GPx, SOD, and CAT concentrations and intracellular transcriptomic levels of SOD and CAT genes were assessed. GSH and taurine supplementation improved the sperm’s kinetics by reducing cooling-associated stress, which was ascertained by lowering MDA concentration and increasing SOD, CAT, and GPx concentrations (P < 0.05). Increasing the levels of antioxidant enzymes in the extender was due to the increasing mRNA copies of the SOD and CAT genes (P < 0.05). Furthermore, GSH and taurine maintained the fructose levels in the extender and lowered the GPT levels, which implies sperm membrane stability is maintained through GSH and taurine supplementation. GSH and taurine supplementation to the extender had protective influences on the in vitro rabbit semen quality during chilled storage for up to 72 h, which were remarkable with increasing supplementation dose and cooling time at 5°C.